2015
DOI: 10.1002/lary.25376
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin protects inner ear against radiation damage in rats

Abstract: These results indicate that melatonin may have significant ameliorative effects on cochlear damage secondary to ionizing radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 36 publications
0
9
0
3
Order By: Relevance
“…In addition, α-lipoic acid (LA) is an endogenously produced co-factor of an enzyme that plays an important role in α-ketoacid dehydrogenase reactions [ 8 , 9 ]. MLT and LA are both effective endogenous ROS scavengers that have been shown to provide protection against IR injury [ 10 , 11 , 12 , 13 ]. In this study, LA was used as the substrate to synthesize a new compound by inserting the MLT amino acid functional groups related to anti-radical, anti-radiation, and immune activity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, α-lipoic acid (LA) is an endogenously produced co-factor of an enzyme that plays an important role in α-ketoacid dehydrogenase reactions [ 8 , 9 ]. MLT and LA are both effective endogenous ROS scavengers that have been shown to provide protection against IR injury [ 10 , 11 , 12 , 13 ]. In this study, LA was used as the substrate to synthesize a new compound by inserting the MLT amino acid functional groups related to anti-radical, anti-radiation, and immune activity.…”
Section: Introductionmentioning
confidence: 99%
“…DPOAE amplitudes both in a and b groups reached better values than they did in group d. Microscopically, damage to the organs of Corti, spiral ganglions, and stria vascularis damage was reduced in both a and b groups when compared with the group c. 5 mg/Kg/day 5 days [51] 50 guinea pigs divided into 5 groups, exposed to 60 h of continuous wide band noise at high intensity (except Comparing group b with a, it was found that the malondialdehyde activity of the plasma and tissue 20 mg/Kg/day 2.5 days (a) control group (not treated and not exposed); (b) exposed to noise and not treated group; (c) exposed to noise and treated with melatonin; (d) exposed to noise and treated with methylprednisolone; (e) exposed to noise and treated with melatonin and methylprednisolone.…”
Section: Igf-1mentioning
confidence: 77%
“…Normal OAE reappeared within 5 days when gentamicin or tobramycin was administered in combination with MT, without interference with the antibiotic function of aminoglycosides [50]. In addition, one study showed that administration of MT after or even before ionizing radiation might prevent high frequency hearing loss [51]. [52] gave an explanation of its effectiveness.…”
Section: Tinnitus: Otoprotective Properties Of Melatoninmentioning
confidence: 99%
“…Paraffin-embedded specimens were cut into 5-6-µm thick sections, mounted on slides and stained with hematoxylin and eosin. [17] Sections of tympanic bullae were examined using a Nikon Optiphot-2 light microscope and analyzed using the Nikon DS-L3 Image Analysis System (Nikon Corporation, Tokyo, Japan). Tissue alterations in each specimen were assessed in the organ of Corti, stria vascularis and spiral ganglia by an experienced histologist who was blinded to the groups.…”
Section: Methodsmentioning
confidence: 99%